(untitled) (Journal of Atomic and Molecular Sciences, 2011)
Bound state solutions of the s-wave Klein-Gordon equation with spatially dependent exponential-type mass for exponential-type scalar and vector potential are studied by using the Nikiforov-Uvarov method. The wave functions of the system are taken on the form of the Laguerre polynomials and the energy spectra of the system are discussed. In limit of constant mass, the wave functions and energy eigenvalues are in good agreement with the results previously.